2006
DOI: 10.1111/j.0909-725x.2006.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastic compression stockings on oedema prevention in healthy controls evaluated by a three‐dimensional measurement system

Abstract: Oedema develops easily in order of the foot, the ankle and the calf in healthy populations. Elastic stockings, even with a pressure as low as 8 mmHg, are effective on oedema prevention. In measurement at the foot, further developments are necessary to improve this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…2 and 4a) and the total Figure 4 Reciprocal of extracellular water resistance (1/R ECW , a) and extracellular to intracellular water ratio (ECW/ICW, b) measured before and after an application of compression stockings. These changes were opposite to those from morning to evening studied in the subgroup of participants (Table 2) as well as reported in the literature (Stick et al, 1985;Seo et al, 1997;Brijker et al, 2000;Kraemer et al, 2000;Jonker et al, 2001;Partsch et al, 2004;Hirai et al, 2006Hirai et al, , 2012Belczak et al, 2010). The right panel shows the percent change expressed as mean and SD (n = 20).…”
Section: Effect Of Compression Stockings On Leg Swellingsupporting
confidence: 70%
See 2 more Smart Citations
“…2 and 4a) and the total Figure 4 Reciprocal of extracellular water resistance (1/R ECW , a) and extracellular to intracellular water ratio (ECW/ICW, b) measured before and after an application of compression stockings. These changes were opposite to those from morning to evening studied in the subgroup of participants (Table 2) as well as reported in the literature (Stick et al, 1985;Seo et al, 1997;Brijker et al, 2000;Kraemer et al, 2000;Jonker et al, 2001;Partsch et al, 2004;Hirai et al, 2006Hirai et al, , 2012Belczak et al, 2010). The right panel shows the percent change expressed as mean and SD (n = 20).…”
Section: Effect Of Compression Stockings On Leg Swellingsupporting
confidence: 70%
“…In each panel, small grey circles represent individual data, whereas a large black circle represents the group mean. On the other hand, the reduction of lower leg volume did not reach statistical significance and was small compared with the prolonged effect of wearing compression stockings found in previous studies (Partsch et al, 2004;Hirai et al, 2006;Belczak et al, 2010;Mosti & Partsch, 2013). lower leg volume tended to decrease (Fig.…”
Section: Effect Of Compression Stockings On Leg Swellingmentioning
confidence: 53%
See 1 more Smart Citation
“…Имеется прямая зависимость улучшения венозной гемодинамики от длительности пользования изделиями [60]. Внедре ние в клиническую практику точных методик изме рения объема конечности, в частности трехмерной оптической системы [61], также позволило показать эффективность эластичных чулок, даже при давле нии ниже 8 мм рт.ст., при профилактике отеков [62].…”
Section: эффективность компрессионной терапии и способы ее оценкиunclassified
“…Compression devices are used with great success to decrease edema in other body parts (Hirai et al, 2006). Several researchers found that venous leg ulcers healed more rapidly in an edematous limb with compression (Escaleira, Cardoso, Rego, Macedo, & Midoes, 2010;O'Meara, Cuilum, & Nelson, 2009).…”
Section: Compressionmentioning
confidence: 99%